Kidney biopsy. Clinicopathological description, complications and evolution in a general hospital in Peru: Biopsia renal. Descripción clinicopatológica, complicaciones y evolución en un hospital general del Perú - Meneses-Liendo, VH (2020)
Introduction: Kidney biopsy is one of the essential tests for the characterization of chronic kidney disease (CKD). Objective: To determine the most frequent primary and secondary glomerulonephritis, complications of renal biopsy and the number of patients on hemodialysis when undergoing renal biopsy. Methods: Observational, descriptive, case series, retrospective and cross-sectional study, carried out at the E. Rebagliati Matins-Peru national hospital. The medical records of patients older than 15 years of age who underwent kidney biopsy between 2008-2016 were reviewed. The data were processed in Stata 16.1 Results: Of 2278 medical records, they corresponded to 1234 women and 1044 men. The most frequent primary and secondary glomerulonephritis were focal and segmental glomerulosclerosis (FSGS) 683 (29.98%) and systemic lupus erythematosus (SLE). ) 434 (19.04%) respectively. Of 1644 biopsied patients, 36 (2.19%) and 241 (14.66%) had major and minor complications respectively. Major complications were more frequent when the procedure was performed by radiology with ultrasound guidance compared to that performed by the nephrologist without ultrasound guidance (p = 0.03694). In 1,324 patients, 329 underwent kidney biopsy while on hemodialysis; of them 43 (13.07%) managed to get out of this therapy and 144 (51.99%) had major or minor complications. Conclusions: GEFyS and SLE were the most frequent primary and secondary glomerulonephritis, respectively. In 1644 patients the major and minor complications were 36 (2.19%) and 241 (14.66%) respectively. In 1,324 patients, 329 (24.8%) were biopsied while on hemodialysis and 144 (51.99%) of them had major or minor complications.